Dietary intake of acrylamide and esophageal cancer risk in the European Prospective Investigation into Cancer and Nutrition cohort - Lujan-Barroso, L; González, C; Slimani, N; Obón-Santacana, M; Ferrari, P; Freisling, H; Overvad, K; Clavel-Chapelon, F; Boutron-Ruault, M; Racine, A; Katzke, V; Kühn, T; et al. (Kluwer Academic Publishers, 2014)
Purpose: The relation between dietary acrylamide intake and esophageal cancer (EC) risk, including esophageal adenocarcinoma (EAC) and esophageal squamous cell carcinoma (ESCC), has not been consistent. We evaluated the association between dietary acrylamide intake and EAC, ESCC, and overall EC in the European Prospective Investigation into Cancer and Nutrition (EPIC) cohort. Methods: Multivariate Cox proportional hazards models were used to estimate the HR and 95 % confidence interval (95 % CI). Since nonlinear relations were observed, HRs were displayed for quartiles of acrylamide intake in μg per day. Results: After a mean follow-up of 11 years, 341 EC were identified, 142 of which were EAC, 176 ESCC, and 23 other histological types or not specified. An increase in EC risk was observed in the second and third quartiles (HR Q2vsQ1 1.75, 95 % CI 1.12-2.74; HRQ3vsQ1 1.66, 95 % CI 1.05-2.61), but not in the fourth quartile, and there was no evidence for a linear dose-response trend. HRs were similarly elevated but not statistically significant when ESCC and EAC were analyzed separately, due to the small number of cases observed. No associations were observed when quartiles were based on energy-adjusted acrylamide intake. Conclusions: In the EPIC cohort, an association between estimated dietary acrylamide intake and an increased risk of developing EC was observed in the middle quartiles but not in the highest quartile; however, results from other larger cohorts or consortia, and results from biomarker studies, might add to the evidence provided by this analysis, suggesting that acrylamide is not an important risk factor for EC. © 2014 Springer International Publishing Switzerland.